2019
DOI: 10.1088/1757-899x/576/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Key technology and equipment for local heating roll-forming of high strength square tube

Abstract: The application of advanced high strength steel and the development innovation manufacturing technology is an effective way to realize the automobile lightweight and improve the safety performance design of high strength steel products. In this paper, a local heating “square to square” roll-forming process was proposed to solve the difficult problems of the introducing high strength steel into the traditional roll-forming equipment. Two kinds of inductors structure were compared and analyzed. Based on the “rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…HRF can break the forming limit of CRF by increasing the ductility of steel materials. However, the previous investigation by Peng et al [30] showed that the microcrack defect occurred during the HRF process of AHSS square tubes while only the influence of heating temperature was studied. Thus, it is necessary to consider the comprehensive influence of various process parameters and obtain the optimization design to improve product quality.…”
Section: Introductionmentioning
confidence: 99%
“…HRF can break the forming limit of CRF by increasing the ductility of steel materials. However, the previous investigation by Peng et al [30] showed that the microcrack defect occurred during the HRF process of AHSS square tubes while only the influence of heating temperature was studied. Thus, it is necessary to consider the comprehensive influence of various process parameters and obtain the optimization design to improve product quality.…”
Section: Introductionmentioning
confidence: 99%